Basal Cell Carcinoma in Type 2 Segmental Darier's Disease - Lynne Robertson; Maxwell B. Sauder (Journal of Skin Cancer)
Background. Darier's disease (DD), also known as Keratosis Follicularis or Darier-White disease, is a rare disorder of keratinization. DD can present as a generalized autosomal dominant condition as well as a localized or segmental postzygotic condition (Vázquez et al., 2002). Clinical features of DD include greasy, warty papules and plaques on seborrheic areas, dystrophic nails, palmo-plantar pits, and papules on the dorsum of the hands and feet. Objective. We report a case of basal cell carcinoma developing in a patient with type 2 segmental DD. Conclusion. According to the current literature, Type 2 segmental disease is a rare presentation of Darier's disease with only 8 previous cases reported to date. In addition, nonmelanoma skin cancer (NMSC) arising from DD is rarely reported; however, there may be an association between DD and risk of carcinogenesis.